2003
DOI: 10.1152/ajpheart.00511.2002
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of TIMP-1 exacerbates LV remodeling after myocardial infarction in mice

Abstract: Recent studies have been directed at modulating the heart failure process through inhibition of activated matrix metalloproteinases (MMPs). We hypothesized that a loss of MMP inhibitory control by tissue inhibitor of MMP (TIMP)-1 deficiency alters the course of postinfarction chamber remodeling and induced chronic myocardial infarction (MI) in wild-type (WT) and TIMP-1(-/-) mice. Left ventricular (LV) pressure-volume loops obtained from WT and TIMP-1(-/-) mice demonstrated that LV end-diastolic volume [52 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 34 publications
(55 reference statements)
7
132
0
2
Order By: Relevance
“…MMP-2 knockout mice also had greater survival after AMI and less left ventricular adverse remodelling (18,46). Selective inhibition of TIMP-1 in TIMP-1 knockout mice has also been shown to exacerbate left ventricular remodelling after AMI (48). The role of TIMP-1 activity alteration was confirmed by Jayasankar et al (49), who demonstrated that in left coronary artery ligation-induced MI in rats, TIMP-1 gene transfer inhibited MMP activity, and preserved cardiac function and geometry in ischemic cardiomyopathy.…”
Section: Mmp Inhibitors and Ami In Animal Modelsmentioning
confidence: 99%
“…MMP-2 knockout mice also had greater survival after AMI and less left ventricular adverse remodelling (18,46). Selective inhibition of TIMP-1 in TIMP-1 knockout mice has also been shown to exacerbate left ventricular remodelling after AMI (48). The role of TIMP-1 activity alteration was confirmed by Jayasankar et al (49), who demonstrated that in left coronary artery ligation-induced MI in rats, TIMP-1 gene transfer inhibited MMP activity, and preserved cardiac function and geometry in ischemic cardiomyopathy.…”
Section: Mmp Inhibitors and Ami In Animal Modelsmentioning
confidence: 99%
“…1,22 Transgenic TIMP-1 Ϫ/Ϫ mice have increased end-diastolic LV volumes, increased end-diastolic LV pressures, and decreased contractility after MI. 23 In addition, chronic myocardial MMP-1 overexpression leads to marked systolic and diastolic cardiac dysfunction in animal models. 24 Transgenic MMP-9 Ϫ/Ϫ mice have reduced LV remodeling and rupture after MI, 25 suggesting that enhanced post-MI MMP activity is an important contributor to subsequent morbidity and mortality.…”
Section: Jayasankar Et Al Timp-1 Gene Transfer Treats Ischemic Cardiomentioning
confidence: 99%
“…The second system involved in ECM remodeling in the heart is the matrix metalloproteinase (MMP)/tissue inhibitor of metalloproteinase (TIMP) system [14]. In the failing heart, down-regulation of TIMPs alters the ECM equilibrium toward matrix degradation and leads to an increase in tissue turnover and accelerated remodeling [15].…”
mentioning
confidence: 99%